Barbershop trend information system - opal m naufal reza; Dedi Haryanto (International Journal Cister, 2022)
This research has a purpose to determine the performance and customers expectations about the service quality of Real7 Barbershop which expected by customers after receiving services from Real7 Barbershop and what should be improved in the services provided by Real7 Barbershop. The samples are taken using simple random sampling method. Simple random sampling is a sampling design in which every single element in the population has a known and equal probability to be selected as a subject. Data analysis are in this research using Analysis of Importance Performance. The results of this research prove that the level of customer expectations of service quality in Real7 Barbershop Yogyakarta is 3.78, where the value is in the condition of customers have high expectations of service quality in Real7 Barbershop Yogyakarta. While, the level of customer performance service quality in Real7 Barbershop Yogyakarta is 4.15, where the value is in good condition of the customer service quality at Real7 Barbershop Yogyakarta. From the servqual analysis results all items are in a positive gap so that customers are satisfied with the quality of services provided by Real7 Barbershop. Conclusively, the five-dimensional servqual value is positive, which indicated that, the overall quality of the service provided by the firm (Real7 Barbershop) meets customer expectations. Factors that must be modified are in quadrant 1, which is the comfort level of the waiting room and the level of cleanliness.